2014
DOI: 10.1117/12.2060957
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous and heterogenized iridium water oxidation catalysts

Abstract: The development of an efficient catalyst for the oxidative splitting of water into molecular oxygen, protons and electrons is of key importance for producing solar fuels through artificial photosynthesis. We are facing the problem by means of a rational approach aimed at understanding how catalytic performance may be optimized by the knowledge of the reaction mechanism of water oxidation and the fate of the catalytic site under the inevitably harsh oxidative conditions. For the purposes of our study we selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Molecular [1] and material [2] water oxidation catalysts (WOCs) with remarkable performances have been reported. Furthermore, it has been recently shown that anchoring a properly tailored homogeneous catalyst onto solid supports, thus obtaining heterogenized WOCs, is a promising strategy to combine the best of two worlds; [5][6][7][8] this allows to finely modulating electron density and geometry of WOCs, whereas grafting the latter on solid supports leads to enhanced stability and facilitates catalyst recovering. [5] At the same time, heterogenized WOCs allow the exploitation of metal to be minimized due to the elevate percentage of active centers, in principle, not so different than that in homogeneous catalysis.…”
mentioning
confidence: 99%
“…Molecular [1] and material [2] water oxidation catalysts (WOCs) with remarkable performances have been reported. Furthermore, it has been recently shown that anchoring a properly tailored homogeneous catalyst onto solid supports, thus obtaining heterogenized WOCs, is a promising strategy to combine the best of two worlds; [5][6][7][8] this allows to finely modulating electron density and geometry of WOCs, whereas grafting the latter on solid supports leads to enhanced stability and facilitates catalyst recovering. [5] At the same time, heterogenized WOCs allow the exploitation of metal to be minimized due to the elevate percentage of active centers, in principle, not so different than that in homogeneous catalysis.…”
mentioning
confidence: 99%